2023
DOI: 10.1186/s12882-023-03081-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between anemia and serum Klotho in middle-aged and older adults

Abstract: Background The role of Klotho as a multifunctional protein in anemia is unclear. This study aimed to determine the association between anemia and serum Klotho concentrations in middle-aged and elderly populations. Methods In this cross-sectional study, we used data collected from the National Health and Nutrition Examination Survey (NHANES) 2007-2016. A total of 13,357 individuals who received serum Klotho measurements, biochemical tests, and demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Klotho is known as an anti-aging gene, and the expression of the Klotho gene decreases with age 35,36 . Moreover, many studies on Klotho in elderly-related diseases indicate that a decrease in serum Klotho levels may contribute to the prevalence of certain chronic conditions in the elderly population [37][38][39] . Therefore, it is speculated that a decrease in Klotho levels is unfavorable for inhibiting aging, and serum Klotho levels are negatively correlated with the prevalence of hypothyroidism in elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Klotho is known as an anti-aging gene, and the expression of the Klotho gene decreases with age 35,36 . Moreover, many studies on Klotho in elderly-related diseases indicate that a decrease in serum Klotho levels may contribute to the prevalence of certain chronic conditions in the elderly population [37][38][39] . Therefore, it is speculated that a decrease in Klotho levels is unfavorable for inhibiting aging, and serum Klotho levels are negatively correlated with the prevalence of hypothyroidism in elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies on larger samples of elderly patients are necessary to confirm these findings [73]. A study by Chencheng et al [68] suggested that low serum Klotho levels were associated with an increased likelihood of anemia in middle-aged and older adults regardless of kidney disease.…”
Section: Erythropoiesis Suppressionmentioning
confidence: 97%
“…The Klotho enzyme, which is mainly expressed in humans in the kidney and brain by the KL gene, especially its alpha-Klotho variant activated by fibroblast growth factor 23 (FGF23), has been indicated as another potential cause of inflammatory anemia in old age [66,67]. Most of the early as well as current studies have focused on the role of alpha-Klotho in chronic kidney disease (CKD) in elderly populations, and reported an age-related Klotho reduction and association with increased likelihood of anemia [68]. Klotho is involved in hematopoiesis regulation through its impact on the hypoxia-inducible factor (HIF1α) pathway.…”
Section: Erythropoiesis Suppressionmentioning
confidence: 99%